Analysis of Character Education Values on the Learning Achievement of Elementary School Teacher Candidates - Imawan, Okky Riswandha; Ismail, Raoda (EDUPEDIA Publisher, 2023)
An elementary school teacher should have good character first to be able to educate the character of his students. The education curriculum for prospective Indonesian elementary school teachers in Indonesia should include character education in order to produce character-educated graduates. The Association of Lecturers of Education for prospective Indonesian Elementary School Teachers has formulated learning outcomes according to the current curriculum. It is necessary to evaluate the formulation of Learning Outcomes adopted by all prospective Indonesian Elementary School Teacher Education study programs. The purpose of this study is to reveal the content of character values ​​in the formulation of learning outcomes for Indonesian elementary school teacher candidates in Indonesia, their suitability with the cognitive approach in character education, and suitability with the socio-cognitive approach in character education. This research is a content analysis research with a qualitative approach through four stages, namely data acquisition, data reduction, inference, and data analysis. The object of this research is the educational learning achievement formula book for prospective Indonesian elementary school teachers published in 2015. The unit of analysis is the character values contained in the educational learning achievement formula book for prospective Indonesian elementary school teachers. The results showed that there were 11 values ​​out of a total of 16 target values ​​in character building at the tertiary level, namely obedience to worship, responsibility, discipline, work ethic, independence, synergy, justice, critical, creative and innovative, compassion and concern, and nationalism, apart from that the formulation of learning outcomes is also in accordance with the cognitive approach in character education which has been listed on the general skills aspect which corresponds to Level 6 of moral development (Kohlberg's cognitive approach), besides that the formulation of learning achievements is in accordance with the approach socio-cognitive in character education has been listed on the affective aspect.